Posted by **Jin** on Thursday, August 19, 2010 at 8:19pm.

how does

secx(tanx + tan^2x- sec^2x)

simplified to

sec x (tanx -1)?

## Answer this Question

## Related Questions

- calculus - find dy/dx y=ln (secx + tanx) Let u= secx + tan x dy/dx= 1/u * du/dx ...
- Pre-Cal - Perform the addition or subtraction. tanx - sec^2x/tanx tan^2(x)/tan(x...
- Calculus - Int tanx sec^2x dx can be taken as (by putting it in form of Int xdx...
- Calculus - Integration - Hello! I really don't think I am understanding my calc ...
- Calc - Hello im trying to integrate tan^3 dx i have solved out the whole thing ...
- Calc - Hello im trying to integrate tan^3 dx i have solved out the whole thing ...
- Calculus - find the derivative of f(x)=tanx-4/secx I used the quotient rule and ...
- calculus - Did I do this problem right? Find the first and second derative-...
- Trigonometry - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b...
- Trigo - Given that a^2+b^2=2 and that (a/b)= tan(45degee+x), find a and b in ...